Assessment of blood one-carbon metabolism indexes during mid-to-late pregnancy in 397 Chinese pregnant women - Zhang, Rong; Wu, Xiangyi; Lu, Lu; Hu, Rui; Teng, Yue; Pan, Lina; Zeng, Xiaoling; Jiang, Wei; Li, Wei; Dong, Ling; Zhu, Wenli (Frontiers in Nutrition, 2024)
One-carbon metabolism (OCM) significantly influences fetal growth and neurodevelopment through transferring methyl group to biomolecules, during which folate, methionine, choline and betaine function as methyl donor nutrients, while vitamin B2, B6, B12 function as enzyme cofactors, and homocysteine (Hcy) and S-adenosyl methionine (SAM) are functional metabolites. This study aimed to assess blood OCM index levels and explore their relationships among Chinese pregnant women. Data were obtained from the baseline of the Mother-Child Nutrition and Health Cohort Study. Pregnant women, recruited from September 2020 to June 2022 during antenatal examinations in China at 24-32 gestational weeks, provided fasting venous blood samples. Measurements included RBC and serum folate, serum vitamin B2, B6, B12, choline, betaine, methionine, total Hcy (tHcy), and plasma SAM. SDC and pregnancy-related conditions were collected via a self-designed questionnaire. Of 397 participants, 82.6% were in mid-pregnancy (24-27 gestational weeks) and 17.4% were in late-pregnancy (28-32 gestational weeks). Serum folate, vitamin B6, and B12 deficiencies were 2.5%, 1.3%, and 8.3%, respectively. Elevated tHcy (≥10 μmol/L) was observed in 1.8% of pregnant women. Elderly pregnant women (aged 35 and above) exhibited lower serum methionine levels (P<0.05), while multiparous women had lower RBC folate levels (P<0.05), and lower serum methionine and vitamin B12 levels (P<0.10, not statistically significant). Partial correlation analysis revealed positive associations between RBC folate and cofactor vitamin B12 (r = 0.244, P<0.05) in the folate cycle, as well as significant correlations between two methyl donor paths [serum folate was significantly related to serum choline (r = 0.172) and betaine (r = 0.193)]. Serum tHcy exhibited negative associations with RBC folate (β = -0.330, P<0.05) and vitamin B6 (β= -0.317, P<0.05), and plasma SAM displayed a positive association with serum betaine (β = 0.610, P<0.05), while negatively associated with serum vitamin B6 (β = -0.181, P<0.05). The blood OCM exhibited imbalances during mid-to-late pregnancy, characterized by lower levels of folate, vitamin B6, and B12, alongside elevated tHcy levels. Adequate folate and vitamin B6 emerged as significant predictors of lower tHcy levels. This suggests the importance of not only ensuring sufficient folate but also optimizing other OCM-related nutrients throughout pregnancy.